Endolymphatic Sac Surgery for Ménière’s Disease - Current Opinion and Literature Review - García,Maria de Lourdes Flores (2017)
Abstract Introduction The endolymphatic sac is thought to maintain the hydrostatic pressure and endolymph homeostasis for the inner ear, and its dysfunction may contribute to the pathophysiology of Ménière’s disease. Throughout the years, different surgical procedures for intractable vertigo secondary to Ménière’s disease have been described, and though many authors consider these procedures as effective, there are some who question its long-term efficacy and even those who think that vertigo control is achieved more due to a placebo effect than because of the procedure itself. Objective To review the different surgical procedures performed in the endolymphatic sac for the treatment of Ménière’s disease. Data Sources PubMed, MD consult and Ovid-SP databases. Data Synthesis We focus on describing the different surgical procedures performed in the endolymphatic sac, such as endolymphatic sac decompression, endolymphatic sac enhancement, endolymphatic sac shunting and endolymphatic duct blockage, their pitfalls and advantages, their results in vertigo control and the complication rates. The senior author also describes his experience after 30 years of performing endolymphatic sac surgery. Conclusions The endolymphatic sac surgery, with all its variants, is a good option for patients with incapacitating endolymphatic hydrops, providing a high percentage of vertigo control and hearing preservation.